2020
DOI: 10.18592/tarbiyah.v9i2.3519
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Mobile Phone Usage's Shifting Among Students

Abstract: This study aims to identify the use of mobile phones in SMAN 1 Pangalengan. The survey was conducted on 100 students. Data collection using a questionnaire. Data analysis uses quantitative descriptive methods. The results showed students tend to utilize social media such as Facebook, Instagram, and WhatsApp. Other uses for browsing, gaming, and entrepreneurship. Survey results show that 92% of students use WhatsApp to communicate and 82% of students use mobile phones to access social media. This shows the patt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
2
0
1
Order By: Relevance
“…Based on the explanation above, it can be concluded that learning ethics is a process of seeking knowledge carried out by someone which in the process makes him acquire knowledge by paying attention to etiquette, etiquette and manners in the teaching and learning process. Learning ethics as teachings, moral principles, customs, or habits regarding what is appropriate, and good in the learning and teaching process (Sutisna, 2020). Student learning ethics is also inseparable from the role of the teacher as an educator who sets an example.…”
Section: Study Ethicsmentioning
confidence: 99%
“…Based on the explanation above, it can be concluded that learning ethics is a process of seeking knowledge carried out by someone which in the process makes him acquire knowledge by paying attention to etiquette, etiquette and manners in the teaching and learning process. Learning ethics as teachings, moral principles, customs, or habits regarding what is appropriate, and good in the learning and teaching process (Sutisna, 2020). Student learning ethics is also inseparable from the role of the teacher as an educator who sets an example.…”
Section: Study Ethicsmentioning
confidence: 99%
“…Banyak di antara mereka tidak lagi menghormati guru mereka bahkan dengan sesama teman mereka sering bersikap intoleransi. Literasi mereka semakin rendah dengan menghabiskan waktu-waktu mereka dengan bermain smartphone setiap harinya (Sutisna, 2020).…”
Section: B Etika Hubungan Interpersonal Siswa Dalam Proses Pembelajaranunclassified
“…Ethics is about a person's attitudes or actions (Sutisna, 2020). Ethics is the study of moral standards and their influence on behavior (Dutelle, 2011).…”
Section: Introductionmentioning
confidence: 99%